2019
DOI: 10.1186/s12888-019-2267-4
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of gender effects on depression among cardiovascular disease patients in Palestine

Abstract: Background Among patients suffering from coronary heart disease (CHD) and comorbid depression, women experience a higher burden compared to men. Little is known on the characteristics that differentiate men and women with both diseases and whether these factors mediate gender effects on depression. This study assessed whether women are more likely to suffer from depression and which characteristics mediate gender effects on depression among a cardiac population in Palestine, specifically addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 70 publications
(76 reference statements)
1
8
0
1
Order By: Relevance
“…The remaining 5 depression scales used in the studies in this analysis also can be used as continuous measurements, with higher scores indicating increased severity of depressive symptoms 62,68,74 . Three studies used the Cardiac Depression Scale 49–51 . Three studies used the Patient Health Questionnaire 44,46,54 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 5 depression scales used in the studies in this analysis also can be used as continuous measurements, with higher scores indicating increased severity of depressive symptoms 62,68,74 . Three studies used the Cardiac Depression Scale 49–51 . Three studies used the Patient Health Questionnaire 44,46,54 .…”
Section: Resultsmentioning
confidence: 99%
“…47,48 Four studies included patients with "cardiac diagnoses," which included CHD, HF, atrial fibrillation, and/or arrythmia. [49][50][51][52] One study examined patients who were admitted to a cardiac rehabilitation program with a cardiac diagnosis. 53…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…В палестинском исследовании 2019г у женщин симптомы тяжелой депрессии диагностировались в 1,5 раза чаще, чем у мужчин -28,7 vs 18,8%, что соответствует результатам нашего исследования. В женской популяции преобладали такие психосоциальные факторы, как низкая стрессоустойчивость и самооценка, низкий уровень КЖ, отсутствие высшего образования, курение и гиподинамия, а также наличие коморбидных патологий [7].…”
Section: Discussionunclassified
“…Psychological functioning appears to have a differential effect on health behaviors for men and for women. One study of cardiac patients found that women with cardiovascular disease and comorbid depression were less likely to engage in physical activity compared with their male counterparts ( Allabadi et al, 2019 ). In one particularly striking study, higher levels of anxiety for women were associated with a significant decrease in a score measuring healthy lifestyle (i.e., physical activity, diet, BMI, and alcohol and tobacco consumption) over 20 years.…”
Section: Introductionmentioning
confidence: 99%